Bond Strength of Ceramic and Metal Orthodontic Brackets to Aged Resin-based Composite Restorations - Della Bona, Alvaro; Kochenborger, Ricardo; Di Guida, Luís A. (Current Dentistry, 2019)
Background: Dental resin composites undergo chemical and mechanical degradation. Thus, the orthodontist should evaluate aged composite restoration surfaces to select the appropriate protocol to successfully bond orthodontics accessories. Objective: This study evaluated the shear bond strength (σ) of metal (M) and ceramic (C) brackets bonded to aged resin-based composite restorations (ACR) after different surface treatments. Methods: ACR specimens (N=160) were fabricated and divided into 8 experimental groups (n=20) as follows: Mo (control)- M bonded to ACR; MA- M bonded to ACR after acid etching using 38% phosphoric acid for 20 s (A); MB- M bonded to ACR after surface roughing using a twelve-bladed bur (B); MBA- M bonded to ACR after B and A; Co (control)- C bonded to ACR; CA- C bonded to ACR after A; CB- C bonded to ACR after B; CBA- C bonded to ACR after B and A. All specimens were stored for 24h before σ testing. Data were statistically analyzed using one-way ANOVA and Tukey post-hoc (α=0.05). Fracture surfaces were examined to determine the failure mode. Results: The surface treatments (A, B and BA) produced similar σ values (p>0.05) to ACR when using the same bracket type. M bracket showed greater σ than C bracket (p<0.05), probably because of different mechanical retention inherent from bracket type. Inhomogeneous stress distribution generated complex failures. Conclusion: Considering the needs of an orthodontic treatment and the surface treatments evaluated, sufficient bond strength was produced to ACR, irrespective of bracket type.
Keywords: Resin-based composite